All-cause community acquired pneumonia cost by age and risk in real-world conditions of care in Spain. (4th July 2022) - Rejas, Javier; Sicras-Mainar, Antoni; Sicras-Navarro, Aram; Lwoff, Nadia; Méndez, Cristina
ABSTRACT: Background: Economic burden of community-acquired pneumonia (CAP) is recognized. Few studies have documented such burden in adults stratified by age, risk status, and by care setting. Spanish data available is scarce. Method: A retrospective, multicenter study in seven regions of Spain (2017–2019) was conducted. Patients ≥18 years with a primary all-cause CAP episode diagnosis were identified. Episode-level variables included risk-stratum based on presence of an immunocompromising/chronic condition, age, number and length of hospitalized and outpatient episodes, and CAP-related healthcare costs/sick leaves were included. Results: 7, 108 episodes [mean age (SD): 59.2 (19.6), 50.42% male, 31.0% hospitalized] were analyzed. Low-risk group accounted for 47.7% of all CAP episodes, 31.5% moderate-risk and 20.8% high-risk. Pneumococcus was identified in 42.2% of cases. Mean CAP episode length was 22.9 days for hospitalized and 13.7 days for outpatient episode. Total healthcare cost for episode was higher in inpatient vs. outpatient: €3, 955 vs. €511, p < 0.001, with higher sick leave cost (€3, 281 vs. €2, 632, p < 0.001), respectively. Conclusion: CAP required hospitalization cost is high regardless of age or comorbidities for the Spanish NHS. Given that almost half of the patients in this study did not have traditional risk factors for CAP, better preventative strategies should seriously be considered.